GE_GERICHTE C/1622/2012 vom 6. Juni 2013 - GE Cour de justice (2013)
MESURE PROVISIONNELLE; DROIT DE GARDE; OBLIGATION D'ENTRETIEN; ALLOCATION FAMILIALE | CPC.148; CPC.276.1; CC.273.1; CC.276; CC.285.1